2003
DOI: 10.1103/physrevlett.91.087001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Penetration Depth Measurements ofPr2xCexC

Abstract: We report measurements of the inverse squared magnetic penetration depth, λ −2 (T ), in Pr2−xCexCuO 4−δ (0.115 ≤ x ≤ 0.152) superconducting films grown on SrTiO3 (001) substrates coated with a buffer layer of insulating Pr2CuO4. λ −2 (0), Tc and normal-state resistivities of these films indicate that they are clean and homogeneous. Over a wide range of Ce doping, 0.124 ≤ x ≤ 0.144, λ −2 (T ) at low T is flat: it changes by less than 0.15% over a factor of 3 change in T , indicating a gap in the superconducting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 24 publications
7
51
0
Order By: Relevance
“…Later mutual inductance measurements on PCCO thin films have shown a variety of temperature dependencies ranging from 3 T to T and, more recently, exponential, depending upon the method of film growth and existence of a buffer layer. [109] Our own measurements on laser ablated thin films of PCCO continue to show power law behavior that depends upon the oxygen doping level. [193] Figure 7 shows data for optimally doped PCCO film and the fit to the disordered d-wave behavior, Eq.…”
Section: Electron-doped Cupratesmentioning
confidence: 83%
“…Later mutual inductance measurements on PCCO thin films have shown a variety of temperature dependencies ranging from 3 T to T and, more recently, exponential, depending upon the method of film growth and existence of a buffer layer. [109] Our own measurements on laser ablated thin films of PCCO continue to show power law behavior that depends upon the oxygen doping level. [193] Figure 7 shows data for optimally doped PCCO film and the fit to the disordered d-wave behavior, Eq.…”
Section: Electron-doped Cupratesmentioning
confidence: 83%
“…Pairing symmetry of electron-doped high-T c cuprate superconductors such as Nd 2−x Ce x CuO 4 and Pr 2−x Ce x CuO 4 is a long standing problem [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17]. Although no consensus has been reached yet, more and more recent experimental results have suggested that the order parameter of electron-doped cuprates is likely to have d x 2 −y 2 -wave pairing symmetry [1,2,3,5,9,10,14,16,17], in close resemblance to that of hole-doped materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Raman scattering [10] and recent ARPES [11] experiments show a nonmonotonic d-wave order parameter. However, this has been contrasted by tunnelling [12,13] and some other specific heat [14] and penetration depth measurements [15,16,17]. In particular, there may be a crossover from d-wave to s-wave symmetries by changing the doped electron concentration [18,19] or decreasing temperature [20].…”
Section: Introductionmentioning
confidence: 99%